The effect of autogenic relaxation techniques on reducing blood pressure in hypertension patients at Bhakti Husada Cikarang Hospital - Nurdini, Rini; Habibah, Ummu (Institute Of Computer Science (IOCS), 2024)
Hypertension was a health problem in all parts of the world and was one of the main risk factors for cardiovascular disease. Data from the National Health Indicator Survey (Sirkesnas) showed an increase in the prevalence of hypertension in Indonesia in the population aged 18 years and over by 32.4% (Riskesdas, 2018). Patients with hypertension cannot only depend on medication, but there must be many nursing actions that can enable patients to be independent in overcoming their problems. One thing that can be done is relaxation techniques. The aim of this study was to determine the effect of blood pressure on patients with hypertension at Bhakti Husada Hospital, Cikarang. This research used a quasi-experimental design, Pretest-Posttest one Group design. The samples taken were all patients treated at Bhakti Husada Hospital with hypertension. The results of data analysis showed that those aged 40-60 years dominated with a percentage of 60.9%, women with 78.3%, secondary education (SMP, SMA) 56.5% and long history of hypertension when treated, dominated by 0-5 years with a percentage of 60.9%. In this study, it was found that blood pressure decreased after autogenic relaxation training by 60.9%. This research also obtained results that there was a significant effect of autogenic relaxation treatment on reducing blood pressure with a p value of 0.000. Suggestions for nurses to utilize non-pharmacological treatment in the form of autogenic relaxation exercises which can be taught to patients and patients can do it independently without having to rely on heart medication.